2017
DOI: 10.1039/c7cc00388a
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous phase transition of hexagonal wurtzite CoO: application to electrochemical and photoelectrochemical water splitting

Abstract: The addition of water initiates the phase transition of hexagonal CoO to Co(OH) nanocrystals. Inducing the phase transition of h-CoO on various substrates results in efficient chemical bonding between Co(OH) and the substrate. The efficient deposition of Co(OH) is widely applicable for electrochemical and photoelectrochemical water oxidation reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
1
8
1
Order By: Relevance
“…Then, we washed the sample with ethanol, collected the solid products by centrifugation, and dried it in an oven at 70 °C for 1 h. The pXRD‐pattern in Figure shows the typical reflections of hexagonal cobalt hydroxide Co(OH) 2 in Brucite‐type layered structure (ICSD PDF‐number 01‐074‐1057) and of hexagonal wurtzite structure, leading to the conclusion, that the material is, at least at the surface, transformed to Co(OH) 2 . The formation of Co(OH) 2 is in agreement with the findings of Jang et al, who reported that hexagonal cobalt oxide transforms spontaneously to hexagonal cobalt hydroxide in contact with water . Though, it is to mention that the incorporated Zn 2+ seems to stabilize the hexagonal structure and prevents a fast conversion.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Then, we washed the sample with ethanol, collected the solid products by centrifugation, and dried it in an oven at 70 °C for 1 h. The pXRD‐pattern in Figure shows the typical reflections of hexagonal cobalt hydroxide Co(OH) 2 in Brucite‐type layered structure (ICSD PDF‐number 01‐074‐1057) and of hexagonal wurtzite structure, leading to the conclusion, that the material is, at least at the surface, transformed to Co(OH) 2 . The formation of Co(OH) 2 is in agreement with the findings of Jang et al, who reported that hexagonal cobalt oxide transforms spontaneously to hexagonal cobalt hydroxide in contact with water . Though, it is to mention that the incorporated Zn 2+ seems to stabilize the hexagonal structure and prevents a fast conversion.…”
Section: Resultssupporting
confidence: 90%
“…Detection of Co(OH) 2 and wurtzite crystal structures after 90 min in 1 m KOH is in contrast to the previously reported rapid total conversion of hexagonal CoO and points to a stabilizing influence of Zn . It further proves that Co(OH) 2 is an important intermediate in the electrochemical formation of γ‐Co(O)OH.…”
Section: Resultscontrasting
confidence: 64%
See 1 more Smart Citation
“…Concerning wurtzite‐CoO, more systematic studies have only recently been carried out. In particular, wurtzite‐CoO has been found to be rather stable in nanoparticle form and has been reported to have appealing catalytic, optical, semiconducting, electrochemical, and biomedical properties, with possible applications in lithium batteries, solar energy conversion, photoacoustic imaging, and water splitting . In addition, this structure has been shown to appear as a strain relief or polarity compensation phase in rock salt‐CoO thin films, as phase separation in Co‐doped ZnO ultrathin films and in passivation CoO shells of Co nanoparticles .…”
Section: Introductionmentioning
confidence: 99%
“…[1] When the h-CoO nanocrystals were spin-coated onto interdigitated electrodes, and then deionized water was added, the conversion from h-CoO to -Co(OH)2 took place at room temperature. [5] Consecutively, the -Co(OH)2 nanoplates were annealed at 300 °C for 2 h under an atmospheric pressure of air to yield spinel Co3O4 nanoplates. And the gas sensing properties of synthesized Co3O4 nanoplates were measured using a computer-controlled characterization system which included a The synthetic approach of Co3O4 nanoplates involved three sequential reactions; preparation of h-CoO, phase transition to Co(OH)2, and oxidation (Fig.…”
Section: Methodsmentioning
confidence: 99%